Treatment with insecticide and fungicide on the physiological quality of lentil seeds - Rubert,J. (2023)
Abstract The low Brazilian productive index and the high demand have aroused interest in the cultivation of lentils, however the legume is little known and needs further studies. The objective of this study was to analyze and identify the effects of treatments with insecticides and fungicides on the physiological quality of lentil seeds, CA-1512 strain. The experiments were conducted in the seed laboratory in a completely randomized design with seven treatments and four replicates. Seed treatment with Thiophanate-methyl; Fluazinam® (180 ml) + Pyraclostrobin; Thiophanate-methyl; Fipronil® (150 ml) promoted higher levels of germination under accelerated aging, lower number of abnormal seedlings and longer lengths of shoot and radicle for the emergence in paper. Treatment with Carboxin; Thiram® (250 ml) + Imidacloprid® (150 ml) allowed a higher value in the first count of germination in sand, lower number of dead seeds under accelerated aging and longer root length, in the emergence in sand. Shoot length in the emergence in sand increased after seed treatment with Metalaxyl-M; Fludioxonil® (75 ml) + Pyraclostrobin; Thiophanate-methyl; Fipronil® (150 ml). Treatments with fungicides and insecticides considerably improved the physiological properties of the seeds, thus being able to guarantee greater phytosanitary qualities in the field, generating healthier seedlings and with protection against possible pests and diseases, and consequently guaranteeing greater productivity.